Analysis of Green Supply Chain Management Performance Measurement in the Tofu Processing Industry (Case Study: Kampung Tahu-Tempe Selili) - Airlangga, Rega Yuni; Wahyuda, Wahyuda; Sitania, Farida Djumiati (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
Kampung Tahu-Tempe Selili is one of the industrial areas in Samarinda City that produces tofu and tempeh. In the production activities of this area, waste is still dumped into the Mahakam River. The problems include improper raw material sourcing, pollution that disturbs the surrounding residents due to the production process, lack of waste management, and the presence of defective tofu either after production or during delivery to consumers. The research Objective is to improve the supply chain activities using the Green Manufacturing approach. This study utilizes the Green Supply Chain Operations Reference (GreenSCOR) model with a focus on the production process. There are 8 Green Objectives with 15 Key Performance Indicators (KPIs) that will be weighted for each KPI using the Analytical Hierarchy Process (AHP) method. Furthermore, data on the actual realization values of the KPIs are collected from 25 factories located in Kampung Tahu-Tempe Selili. The calculation is performed using the Snorm de Boer method to normalize the actual data, and the Traffic Light System (TLS) method is used to categorize the KPI performance. Based on the calculation of weights and normalization values, the performance score of Kampung Tahu-Tempe Selili is 69.85, KPIs MR-03 and MR-04 are problems faced by all factories and are categorized as red. Factory conditions that cannot treat liquid waste and waste in water use, so that steps that can be taken by the factory reuse residual water for needs that do not involve direct contact with food which can reduce water demand. Then work with the local government to build a waste end treatment plant which can later be processed into alternative biogas fuel.